Learning sufficient representation for spatio-temporal deep network using information filter - Hu Y.; Neoh D.T.H.; Sahari K.S.M.; Loo C.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
This article introduced an improved spatio - temporal deep network based on information filter method for learning sufficient representation. The proposed method aims to improve feature learning capability while modeling spatial and temporal dependencies. Experiments on pattern recognition are conducted to validate the effectiveness of the proposed method. © 2014 IEEE.